Pendekatan Keadilan Restoratif dalam Penyelesaian Tindak Pidana Kekerasan dalam Rumah Tangga - Aziz, Abdul; Maksum, Ghufron; Mutakin, Ali (Al Ashriyyah, 2023)
This article seeks to explain that the crime of domestic violence does not always have to prioritize criminal action, but rather prioritizes recovery for the interests of the victim through restorative justice, which is an alternative settlement of criminal cases outside the court. Settlement of acts of violence in the household sphere if the criminal law route is resolved is deemed inappropriate, considering that the perpetrator and the victim have a personal and legal relationship, so different ways of solving the conflict in the household are needed, one of which is with a restorative justice approach, on the basis of these legal issues this research was conducted. This research is a normative legal research. Furthermore, it is analyzed through the stages of interpretation, assessment, research, and evaluation. And finally concluded in a descriptive form. From the results of the research it is known that the settlement of acts of domestic violence can be carried out with a restorative justice approach by involving victims, perpetrators and other independent related parties to find the best solution to reach an agreement rather than just imposing a sentence. From the category of acts of domestic violence specified in the Law, it can be carried out with a restorative justice approach with a subjective and proportional assessment of each case and taking into account the agreement between the two parties.